Is ORIF Superior to Nonoperative Treatment in Isolated Displaced Partial Articular Fractures of the Radial Head? - Yoon, Albert (Springer US, 2014)
BACKGROUND: While good results have been reported with both nonoperative and operative treatment of isolated displaced partial radial head fractures, there remains considerable disagreement about the role of surgery in the management of these injuries. QUESTIONS/PURPOSES: We (1) compared isolated displaced partial articular radial head fractures treated nonoperatively with open reduction internal fixation (ORIF) in terms of validated outcomes scores, ROM, and strength; (2) assessed whether there were any predictor variables for outcomes; and (3) compared complications between groups. METHODS: We retrospectively compared patients with isolated partial articular radial head fractures displaced greater than 2 mm but less than 5 mm who received either nonoperative treatment (30 patients) or ORIF (30 patients). We reviewed the nonoperative and ORIF groups at a mean of 3 and 4.5 years, respectively. The nonoperative and ORIF groups were similar except for age (51 ± 17 years versus 39 ± 10 years, respectively) and fracture displacement (2.3 ± 0.3 mm versus 2.8 ± 0.6 mm, respectively). As there were no definitive guidelines on which treatment represented best management, treatment type was decided by the attending surgeon in conjunction with the patient on a case-by-case basis. Patients were evaluated using the Patient-rated Elbow Evaluation (PREE) (primary outcome measure), Mayo Elbow Performance Score (MEPS), QuickDASH, SF-12, clinical examination, and radiographic evaluation (14 and 28 in the nonoperative and ORIF groups, respectively). Elbow ROM was assessed with a goniometer and hand grip strength with calibrated strength testing. We assessed possible predictive variables (age, displacement, energy of injury) for clinical outcome scores and recorded complications. RESULTS: PREE scores were not different between groups, but the MEPS favored the nonoperative group (93 versus 86; p = 0.012). ROM and grip strength were similar between groups. Younger age was associated with worse outcome, but displacement and energy were not. More complications occurred in the ORIF group (eight cases of mild heterotopic ossification, two cases of hardware failure) than in the nonoperative group (one case of mild heterotopic ossification, one case of complex regional pain syndrome). CONCLUSIONS: No clinical benefit with ORIF could be found compared to nonoperative management of isolated partial articular radial head fractures with displacement of greater than 2 mm but less than 5 mm at short-term followup. A well-designed randomized trial and followup at longer term are required to provide better information about how to treat these common fractures. LEVEL OF EVIDENCE: Level III, therapeutic study. See Instructions for Authors for a complete description of levels of evidence.